PERTUMBUHAN BIBIT KEMIRI (Aleurites moluccana L.WILLD) DI LAHAN TERBUKA SETELAH DIBERI PERLAKUAN NAUNGAN DI PERSEMAIAN - Tri Susanto; Basir Achmad; Gusti Syeransyah Rudy (Universitas Lambung Mangkurat, 2021)
The purpose of this study was to analyze the growth of candlenut seeds (Aleurites moluccana L. Willd) in open land after being given shade treatment in the nursery. The method used for observing the growth of candlenut seedlings is a Completely Randomized Design (CRD). The treatment in the nursery was shade levels consisting of 0%, 25%, 50% and 75%. Each treatment consisted of five samples and each treatment was repeated three times so that 4 × 5 × 3 = 60 seedlings were needed. Subsequent research was conducted on open land with 100% sunlight intensity. The parameters measured were height, diameter and number of leaves. Based on observations of candlenut seedlings in open land after being given shade treatment at the nursery for 12 weeks showed that the percentage of seedling life was 80%. The results of the variance analysis showed that the shade treatment significantly affected the growth of candlenut seedling height, but had no effect on the increase in diameter and the number of leaves.Keywords: Candlenut seedling growth; Open land; Shade